Ulinastatin alleviates neurological deficiencies evoked by transient cerebral ischemia via improving autophagy, Nrf-2-ARE and apoptosis signals in hippocampus - Jiang, Xiao-Ming; Hu, Jing-Hai; Wang, Lu-Lu; Ma, Chi; Wang, Xu; Liu, Xiao-Liang (Physiological research, 2018)
Ulinastatin [or called as urinary trypsin inhibitor (UTI)] plays a role in regulating neurological deficits evoked by transient cerebral ischemia. However, the underlying mechanisms still need to be determined. The present study was to examine the effects of UTI on autophagy, Nrf2-ARE and apoptosis signal pathway in the hippocampus in the process of neurological functions after cerebral ischemia using a rat model of cardiac arrest (CA). CA was induced by asphyxia followed by cardiopulmonary resuscitation (CPR) in rats. Western blot analysis was employed to determine the expression of representative autophagy (namely, Atg5, LC3, Beclin 1), p62 protein (a maker of autophagic flux), and Nrf2-ARE pathways. Neuronal apoptosis was assessed by determining expression levels of Caspase-3 and Caspase-9, and by examining terminal deoxynucleotide transferase-mediated dUTP nick-end labeling (TUNEL). The modified neurological severity score (mNSS) and spatial working memory performance were used to assess neurological deficiencies in CA rats. Our results show that CA amplified autophagy and apoptotic Caspase-3/Caspase-9, and downregulated Nrf2-ARE pathway in the hippocampus CA1 region. Systemic administration of UTI attenuated autophagy and apoptosis, and largely restored Nrf2-ARE signal pathway following cerebral ischemia and thereby alleviated neurological deficits with increasing survival of CA rats. Our data suggest that UTI improves the worsened protein expression of autophagy and apoptosis, and restores Nrf2-ARE signals in the hippocampus and this is linked to inhibition of neurological deficiencies in transient cerebral ischemia. UTI plays a beneficial role in modulating neurological deficits induced by transient cerebral ischemia via central autophagy, apoptosis and Nrf2-ARE mechanisms.
Keywords: glykoproteiny; Animals; apoptóza; hipokampus; NF-E2-Related Factor 2; Autophagy; Ischemic Attack, Transient; Apoptosis; Glycoproteins; faktor 2 související s NF-E2; signální transdukce; Signal Transduction; inhibitory trypsinu; Rats, Sprague-Dawley; autofagie; tranzitorní ischemická ataka; Male; potkani Sprague-Dawley; Neuroprotective Agents; Trypsin Inhibitors; krysa rodu Rattus; antioxidační responzivní elementy; Hippocampus; Random Allocation; zvířata; mužské pohlaví; Antioxidant Response Elements; Rats; náhodné rozdělení; neuroprotektivní látky